OPTIMASI PENCAMPURAN ASPAL BUTON DENGAN METODE SIMPLEK UNTUK MEMENUHI KRITERIA PERMINTAAN KONSUMEN DI PT. WIJAYA KARYA BITUMEN SITE KABUNGKA PULAU BUTON PROVINSI SULAWESI TENGGARA - Afrizal Wildan; Fadhilah Fadhilah (Departemen Teknik Pertambangan FT UNP, 2021)
Abstract. In meeting the criteria for consumer demand, PT. Wijaya Karya Bitumen strives to produce products according to consumer desires. Currently, the demand for specific natural asphalt content, namely 21% asphalt content and maximum water content of 2% with a total of 5000 tons makes it difficult for companies to meet these consumer criteria, therefore a mixing formula is needed for natural asphalt with different types of quality to meet consumer demand. The method used to obtain the mixing result was the simplex method with two variables, then the natural asphalt used for mixing was 19% bitumen content and 1.8% moisture content with 24% bitumen content and 2% moisture content. After calculating the results of the calculation of the results of mixing natural asphalt with a mixing ratio of 3: 2, the results of these calculations can be used for mixing natural asphalt following the criteria of consumer demand at PT. Bitumen Wijaya Karya. Keywords: Mixing, Simplek Method, Natural Asphalt, Bitumen, Water.